Cloud data integrity checking methods: a survey - George, Anju; Shajin Nargunam, A. (International Journal of Engineering and Technology, 2019)
Cloud computing is an internet- based computing which provides different services to its users on demand. The users can keep their data in the cloud server without maintaining a native copy. The integrity of the data outsourced can be ensured using various data integrity checking methods. This paper discusses the pros and cons of various techniques for checking data integrity, along with future directions to researchers. The major concern of the data integrity checking methods is the computational load of auditors.Â
Keywords: Auditing Protocols; Cloud Computing; Cloud Storage; Data Integrity; Third -Party Auditor